PENGUATAN PEMASARAN PRODUK BATIK TULIS “MBAH JO” MELALUI STRATEGI PRODUCT BRANDING - Andri Wahyu Utomo; Shelly Merlyana Putri Meylani, Siska Lutfi Emiliana, Aulia Permatasari (CV. ADIBA AISHA AMIRA, 2023)
The